The nonlinear effect of uncertainty in portfolio flows to Mexico - Marco Hernández Vega (Banco de México, 2021)
Economic uncertainty is considered not only one of the main causes of recessions, but also a major obstacle to economic recovery. Recent studies find that significantly high levels of uncertainty could have a non-linear impact that amplifies the response of macroeconomic variables. The objective of this document is to analyze the presence of this impact on portfolio flows to Mexico. The results show that episodes of high uncertainty have a greater negative impact on bond and stock flows than those found under a linear VAR. Furthermore, it is observed that the effect is more persistent for bond flows. Finally, high uncertainty leads to a marked depreciation of the nominal exchange rate, a contraction in economic activity and a fall in the stock index.
Keywords: F32; F62; G10; 330; Foreign Portfolio Investment; Mexican Equity and Bond Market; Uncertainty